Considerably enhanced perovskite solar cells via the introduction of metallic nanostructures. Issue 14 (16th March 2017) - Cheng, Yu; Chen, Cong; Chen, Xu; Jin, Junjie; Li, Hao; Song, Hongwei; Dai, Qilin
Abstract : Metallic nanostructures are used to improve the perovskite solar cell performance by light scattering, and Au–Ag alloy nanostructures show a considerable enhancement. Abstract : Currently, perovskite solar cells (PSCs) are attracting extensive interest due to their potential for overcoming the energy crisis. However, increasing the power conversion efficiency (PCE) of PSCs to realize outdoor applications is still one of the crucial issues in PSC research. In this study, metallic nanostructures including Au, Ag and Au–Ag nanoalloy with different sizes and morphology were synthesized via a chemical solution method and embedded into an electron collecting TiO2 layer in PSCs based on the physical deposition method, which allows control over the incorporation of the metallic-nanostructures. The best improvement in the PCE was obtained using the Au–Ag nanoalloy, exhibiting an efficiency of 14.8%, which increases 17.5% compared to the bare PSCs. We believe that the increased device performance originates from increased light harvesting due to the increased optical path length caused by the light scattering of the metallic nanostructures. This strategy demonstrates a novel way to enhance the performance of photovoltaic devices.